P.Ramlee's music: an expression of local identity in Malaya during the mid-twentieth century - Chan, Clare Suet Ching (Tanjong Malim, 2012)
P.Ramlee's music: an expression of local identity in Malaya during the mid-twentieth century by Chan, Clare Suet Ching